Well plate-based perfusion culture device for tissue and tumor microenvironment replication1. Issue 13 (7th July 2015) - Zhang, W.; Gu, Y.; Hao, Y.; Sun, Q.; Konior, K.; Wang, H.; Zilberberg, J.; Lee, W. Y.
<x xml:space="preserve">Abstract</x> We present a multipurpose 96-well plate-based perfusion culture device for tissue and tumor microenvironment replication.